Pengetahuan Guru PAUD terhadap Beyond Centers and Circle Time - Laylatul Rodiah; Riswanti Rini; Ari Sofia (FKIP UNILA, 2018)
This study aimed to describe the knowledge of PAUD teachers toward Beyond Centers and Circle Time (BCCT) learning model. This study was conducted in Labuhan Maringgai Sub-district, East Lampung with the population 106 teachers. This study was used purposive sampling technique with the consideration of teacher with education background of Senior High School/equal to 46 teachers. The data were collected by tests and documents technique. Data of this study was analyzed by descriptive quantitative. The results showed that most of the teachers do not understand about BCCT learning model, expecially the meaning of BCCT (20% of 46 teachers have understood), BCCT principles (26% of 46 teachers have understood), BCCT steps (13% of 46 teachers have understood), application procedures (15% of 46 teachers have understood) and learning evaluation procedures (26% of 46 teachers have understood).Penelitian ini bertujuan untuk mendeskripsikan pengetahuan guru PAUD terhadap Beyond Centers and Circle Time (BCCT). Penelitian ini dilaksanakan di Kecamatan Labuhan Maringgai Kabupaten Lampung Timur dengan populasi yaitu seluruh guru TK di Kecamatan Labuhan Maringgai yang berjumlah 106 guru. Penelitian ini menggunakan teknik purposive sampling dengan pertimbangan guru yang berlatar belakang pendidikan SMA/sederajat yang berjumlah 46 guru. Teknik pengumpulan data dalam penelitian ini menggunakan tes dan dokumen. Data hasil penelitian ini dianalisis secara deskriptif kuantitatif. Hasil penelitian menunjukkan bahwa sebagian besar guru tidak paham tentang pembelajaran BCCT yang meliputi pengertian BCCT (20% dari 46 guru telah memahami), prinsip BCCT 26%, langkah-langkah 13%, prosedur penerapan 15% dan prosedur evaluasi pembelajaran 26%.Kata Kunci : beyond centers and circle time, pendidikan anak usia dini, pengetahuan guru